ICP - MS ANALYSIS OF RHENIUM AND OSMIUM ISOPTOPES FROM THE COLDWELL ALKALINE COMPLEX - FULTON, GREG (My University, 1990)
This thesis more than most, would probably have coma to nothing without the incredible amount of support of the people around me. Most notably 1 would like to thank my parents for helping me see the flip side of things and for editing above and beyond the call of duty.. Steve, my brother, for putting up with a steady stream of calls complaining about the inadequacy of whatever equipment I was working on at the time. Last but not least, to Shannon who acted as a balm to my fevered brain. As well, I would like to thank Dave Good for the samples, and for keeping a constant interest in what seemed to me to be an unworkab1e beast